PENYEDIAAN TEMPAT SAMPAH UNTUK MENUNJANG KEBERSIHAN LINGKUNGAN MASYARAKAT DI DESA SISOBAWINO II KECAMATAN LOLOFITU MOI - Famatorozokho Dakhi; Azwardin Harefa; Rani Diwisastri Gulo; Dahsyatman Zalukhu; Elti Zidomi; Ica Anjeli Daeli; Maria Dilpan M. Gowasa; Nofirman Waruwu; Novitasari Duha; Mychael Ehowu Daeli; Yurmanius Waruwu (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
Community service conducted by Universitas Nias Raya is implemented through the Community Service Program (Kuliah Kerja Nyata/KKN). The main objectives of this activity are to carry out community service, provide students with real-life experience in social life, strengthen relationships between the university and local government and communities, and support the availability of village data or profiles through identification and analysis that can be utilized for village development planning aligned with the Sustainable Development Goals (SDGs). The KKN program was carried out in several villages in West Nias Regency, one of which was Sisobawino II Village, Lolofitu Moi Subdistrict, from July 12 to August 25, 2025. Sisobawino II Village is known to have shown relatively good development in social, economic, and technological aspects. The implementation of the KKN program began with village observations to identify potentials and issues that became the main focus of the program. The KKN activities were systematically designed through discussions involving the KKN student group, village officials, and the local community. The stages of implementation included planning, execution, and final evaluation. The results achieved included the development of agricultural land, provision of waste bins, installation of decorative flags (umbul-umbul), tutoring assistance for elementary school students, mutual cooperation activities (gotong royong), and participation in enlivening the celebration of the Independence Day of the Republic of Indonesia on August 17, 2025.